Workers`s Rights According to Islamic Law Persepective (The Principle of Mudharabah) That Can Be Applied In Trade and Investment Agreements - Dewi, Gemala (Indonesian Journal of International Law, 2021)
The practice of Foreign Direct Investment (FDI) in developing countries often cause the labor problems, such as the labor on strike demanding higher wages or the severance pay as the results of the “down-sizing” whose made changes etc. In the country who has inadequate labors regulation or even does not have a strong labors union, it is difficult to enforce the rights of the labors. With the extreme separation position system between the labors and the employer, the problem is always decreasing, so the concept of alternative working relationship to solve this problem. The mudharabah principle in working agreement may be the way to solve the problem. That principle puts the labor and the employer to the same position, so the worker can develop their self to be productive and will gain the the profit for the company and also increase the labors income. In that principle, the company does not need “downsizing” or facing the labors “strikes” or “layoffs”, because the labor welfares can directly obtain from the hard work for the company. Besides the welfare for the labors, this concept is also can attract the foreign investment in our country.